Diversity of myxozoans (Cnidaria) infecting Neotropical fishes in southern Mexico - Alama-Bermejo, Gema; Hernández-Orts, Jesús S; García-Varela, Martín; Oceguera-Figueroa, Alejandro; Pecková, Hana; Fiala, Ivan (Scientific reports, 2023)
Myxozoans are a unique group of microscopic parasites that infect mainly fishes. These extremely reduced cnidarians are highly diverse and globally distributed in freshwater and marine habitats. Myxozoan diversity dimension is unknown in Mexico, a territory of an extraordinary biological diversity. This study aimed to explore, for the first time, myxozoan parasite diversity from fishes of the Neotropical region of Mexico. We performed a large morphological and molecular screening using host tissues of 22 ornamental and food fish species captured from different localities of Veracruz, Oaxaca and Chiapas. Myxozoan infections were detected in 90% of the fish species, 65% of them had 1 or 2 and 35% had 3 and up to 8 myxozoan species. Forty-one putative new species were identified using SSU rDNA phylogenetic analyses, belonging to two main lineages: polychaete-infecting (5 species) and oligochaete-infecting (36 species) myxozoans; from those we describe 4 new species: Myxidium zapotecus sp. n., Zschokkella guelaguetza sp. n., Ellipsomyxa papantla sp. n. and Myxobolus zoqueus sp. n. Myxozoan detection increased up to 6 × using molecular screening, which represents 3.7 × more species detected than by microscopy. This study demonstrated that Neotropical fishes from Mexico are hosts of a multitude of myxozoans, representing a source of emerging diseases with large implications for economic and conservation reasons.
Keywords: Parasitic Diseases, Animal; Myxozoa; ribozomální DNA; Myxobolus; nemoci ryb; Fishes; Animals; Mexiko; Cnidaria; Fish Diseases; parazitární nemoci u zvířat; Phylogeny; DNA, Ribosomal; zvířata; fylogeneze; Mexico; ryby